(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: As pecten oculi had great functional significances for ornithology, pecten oculi of Baladi duck was well-deserving of intensive morphological study. So, the aim of this study was to throw light on some anatomical and histological formation of the pecten oculi of Baladi ducks as well as use of scanning electron microscopy. Materials and Methods: Twenty eyeballs of 10 adult Baladi ducks were used to fulfill this work. Ten eyes were used to study the gross anatomy of pecten oculi, including the location, shape, and numbers of pleats. Five samples were embedded at 10% neutral buffered formalin. The specimens were examined by regular histological procedures. The latter five samples were applied for electron microscopy. Results: Grossly, the pecten oculi is formed of three portions: the base, emerged from the optic disk; the pleats, sorted in fan shape; and the bridge. The essential histological ingredients of Baladi ducks’ pecten oculi are the blood vessels, lymph vessels, pigment cells, and hyalocytes. Conclusion: The current work explains the primary macro- and micro-morphological features of pecten oculi in Baladi duck and collates these features to those formerly explained in other birds. Generally, pecten oculi of Baladi duck was analogous to that of the diurnal birds. J. Adv. Vet. Anim. Res., 6(4): 456-462, December 2019